Nivel de conocimiento sobre salud periodontal de estudiantes de ciencias de la salud. Un studio transversal - Aranda Rischmoller, Jackeline (2024)
Introduction: Periodontal disease is a multifactorial chronic inflammatory disease, so knowledge about this disease is important for health professionals for an assertive and early diagnosis. Objective: Determine the level of knowledge about periodontal health in Health Sciences students at a private university in Lima-Perú. Materials and Methods: Through a descriptive and cross-sectional study, 200 students from the Faculty of Health Sciences were evaluated. The sample size was obtained using a proportion estimation formula. The level of knowledge about periodontal health was measured using a specific virtual and self-applicable questionnaire, which was fully validated. University students of legal age and who signed the informed consent were included. This consisted of 16 questions about the causes, signs, prevention habits and relationship with systemic diseases related to periodontal disease. The data were analyzed using descriptive statistics (absolute and relative frequencies) and means and averages for age. Results: The level of knowledge was medium in 38%, high in 32.5% and low in 29.5% of the students surveyed. 96.5% knew that periodontal disease is preventable; However, 91.5% do not know what its main clinical sign is. Conclusions: The use of a self-applicable and specific questionnaire is beneficial to evaluate and measure knowledge about periodontal health, and the Health Sciences students evaluated have a medium level of knowledge about periodontal health.